2008
DOI: 10.1021/jf8000229
|View full text |Cite
|
Sign up to set email alerts
|

A Validated Method for Gas Chromatographic Analysis of γ-Aminobutyric Acid in Tall Fescue Herbage

Abstract: Gamma-aminobutyric acid (GABA) is an inhibitory neurotransmitter in animals that is also found in plants and has been associated with plant responses to stress. A simple and relatively rapid method of GABA separation and quantification was developed from a commercially available kit for serum amino acids (Phenomenex EZ:faast) and validated for tall fescue (Festuca arundinacea). Extraction in ethanol/water (80:20, v/v) at ambient temperature yielded detectable amounts of GABA. Clean separation from other amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In Saccharomyces cerevisiae, GAD is required for normal oxidative stress tolerance [7]. In plants, GABA accumulation has been reported in response to stress conditions such as anoxia, decreasing cellular pH, temperature changes, mechanical handling, and pathogen infections, and it has been associated with plant growth response [5,8]. Furthermore, in plants and microbes, GABA is an important intermediate of the GABA shunt, the metabolic pathway that converts glutamate to succinate, directing the carbon atoms into the Krebs cycle [9].…”
Section: Introductionmentioning
confidence: 99%
“…In Saccharomyces cerevisiae, GAD is required for normal oxidative stress tolerance [7]. In plants, GABA accumulation has been reported in response to stress conditions such as anoxia, decreasing cellular pH, temperature changes, mechanical handling, and pathogen infections, and it has been associated with plant growth response [5,8]. Furthermore, in plants and microbes, GABA is an important intermediate of the GABA shunt, the metabolic pathway that converts glutamate to succinate, directing the carbon atoms into the Krebs cycle [9].…”
Section: Introductionmentioning
confidence: 99%
“…1 It has been suggested that it is involved in the cortical reorganization that follows a limited sensory deprivation. [2][3][4][5] Several techniques, such as magnetic resonance spectrometry, 6 electroanalysis, 7 fluorescence, 8 spectrophotometric, 9 capillary electrophoresis, 10 gas 11,12 and liquid chromatography, 13,14 have been developed for the determination of 4-ABA. The most common method employed for the determination of 4-ABA is liquid chromatography.…”
mentioning
confidence: 99%